The effective components of herbal medicines used for prevention and control of fish diseases. Issue 126 (July 2022) - Zhang, Weini; Zhao, Jinpeng; Ma, Yufang; Li, Jian; Chen, Xinhua
Abstract: The increasing demand for fish consumption has promoted the rapid development of fish aquaculture. With the continuous expansion of culture scale and the deterioration of culture environment, various diseases have broken out frequently, leading to huge economic losses to fish farming. Antibiotics and chemicals are common options to prevent and control of fish diseases, but their use is now restricted or even banned due to serious problems such as drug residues, pathogen resistance, and environmental pollution. Herbs and their extracts have increasingly become promising supplements and alternatives, because of their effectiveness, safety, environmental friendliness and less drug resistance. The application of herbal medicines in prevention and control of fish diseases is mainly attributed to the powerful immune enhancement, antioxidation or direct anti-pathogenic efficacies of their effective components, including mainly polyphenols, polysaccharides, saponins, flavonoids, alkaloids, and essential oils. Recently these herbal active ingredients have been extensively studied for their efficacies in prevention and control of viral, bacterial, parasitic, and fungal diseases in fish. In the present paper, we comprehensively summarize the research progress of the active ingredients of herbal medicines used for prevention and control of fish diseases, especially of their action mechanisms, and highlight the potential application of the herbal medicines in fish aquaculture. Highlights: The bioactive components of herbs have been widely used in prevention and control of fish diseases. Herbal effective components showed powerful antiviral, antibacterial, antiparasitic, and antifungal effects in fish. Herbs' action mechanisms involve immunoenhancing and antioxidant effects on fish, or direct killing efficacies on pathogens.